Isotopic and Hydrogeochemical Characteristics and Genesis of Warm Springs in the Jiangcang Basin, Qinghai, China - Liu, Lingxia; Qi, Shihua; Zhang, Yongbin; Gao, Ming; Hu, Jing; Wang, Wenzhong (Frontiers in Earth Science, 2022)
The Jiangcang Basin is a Cenozoic faulted basin, where many low-temperature warm springs are exposed, with the highest temperature being 36.6°C. The study of the hydrogeochemical characteristics of the geothermal fluids of these warm springs can effectively clarify the genetic mechanisms of the geothermal resources in the Jiangcang Basin and thus is of great significance for the development and utilization of geothermal resources in the Qinghai Province. Using the geothermal and geological conditions of the Jiangcang Basin, this study analyzed the hydrochemical and isotopic characteristics of water samples collected from cold water and from four warm springs in the Jiangcang Basin, obtaining the following results. The four warm springs have the hydrochemical types of HCO3-Ca·Mg, HCO3-Ca·Na·Mg, and HCO3·SO4-Na·Ca and total dissolved solids (TDSs) of 720.4–1,663 mg/L. Moreover, no significant positive correlation is found between Cl− and other ions in the warm springs. The results of isotopic analysis show that the warm springs are mainly recharged by atmospheric precipitation and meltwater from ice and snow, with a recharge elevation of 4,401–4,501 m. Furthermore, the geothermal reservoirs in the Jiangcang Basin have temperatures of 51–83°C and circulation depths of 1,848–2,610 m. Atmospheric precipitation and the meltwater from ice and snow infiltrate downward in high mountain areas and form runoffs along the tectonic channels in the basin. After being heated through deep circulation, they migrate upward along fault fracture zones under the influence of faults and the water blocking of mudstones, during which they cool by thermal conduction and mixing with shallow cold groundwater. Finally, the mixed water is exposed in the form of low-temperature tectonic warm springs. The results of this study can provide data for the exploitation and utilization of geothermal resources in the Qinghai Province.